A homogeneous inhomogeneous polyimide film and its preparation method and application

By introducing crystal orientation and optimized preparation process into the polyimide film, the dielectric performance and hygroscopicity problems of traditional polyimide materials in 5G high-frequency communication are solved, and the polyimide film materials with low dielectric constant, low dielectric loss and low hygroscopicity are achieved, which are suitable for 5G high-frequency communication technology.

CN114479450BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202011156719.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-26
Publication Date
2025-03-04
Estimated Expiration
2040-10-26

AI Technical Summary

Technical Problem

Traditional polyimide materials have problems with dielectric constant, dielectric loss and high hygroscopicity in high-frequency communication technology in the 5G era, and cannot meet the application requirements of high-frequency and high-speed communication.

Method used

Using homogeneous heterogeneous polyimide film material, the molecular chain orientation and grain structure of the material are optimized by introducing partial crystallization into the polyimide film and highly oriented in the direction of the parallel film surface, combining synchronous bidirectional stretching and heat treatment annealing steps.

Benefits of technology

The low dielectric constant, low dielectric loss and low hygroscopic rate of polyimide film are achieved, which is specifically manifested as a dielectric constant <3.0, dielectric loss <0.005, and hygroscopic rate <0.5% at 10GHz frequency, meeting the needs of high-frequency communication technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114479450B_ABST
    Figure CN114479450B_ABST
Patent Text Reader

Abstract

The present invention relates to a homogeneous heterogeneous polyimide film suitable for high-frequency communication technology, a preparation method and use thereof. The crystals in the polyimide film are mainly oriented along a direction parallel to the film surface, the orientation factor is greater than 0.4, and when tested under a frequency of 10 GHz, the dielectric constant is less than 3.0, the dielectric loss is less than 0.005, and the moisture absorption rate is less than 0.5%. The polyimide film can be used in the industrial production of homogeneous heterogeneous polyimide film materials suitable for high-frequency communication technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyimide, in particular to a homogeneous inhomogeneous polyimide film suitable for high-frequency communication technology and a preparation method and application thereof. Background Art

[0002] With the advent of the 5G era, high-frequency communication technologies with ultra-high speed and ultra-high data density will be fully rolled out, and the FR2 frequency band in the 5G technical standard has even reached the range of millimeter waves. Ensuring high-fidelity transmission of such high-frequency electromagnetic waves is a great challenge for the manufacture of electronic devices, especially dielectric materials for signal receiving and transmission components such as antennas. According to the principles of electromagnetics, the higher the frequency of electromagnetic waves, the higher their energy, the stronger their penetration, the higher their penetration loss, and the weaker their diffraction ability. Therefore, in order to ensure high-fidelity transmission of millimeter-wave signals, the dielectric materials in electronic devices must have very low dielectric constants and dielectric losses, so as to minimize the delay and consumption of signals during device transmission.

[0003] Polyimide (PI) is a type of polymer containing an imide ring structure on the main chain of the molecule. It is one of the functional polymer materials with the best comprehensive performance at present, and it is also one of the few polymer materials that can meet the needs of the microelectronics industry. PI materials have always been one of the most important basic materials in the microelectronics industry. PI films, adhesives, etc. are widely used in the manufacture and packaging of microelectronic devices. However, with the gradual application and promotion of 5G technology, traditional PI substrates have problems with high dielectric constant, dielectric loss and hygroscopicity, and can no longer meet the application requirements of high-frequency and high-speed communications in the 5G era. Therefore, it is urgent to develop new PI materials with low dielectric constant, low dielectric loss and low moisture absorption to meet the technical requirements of high-frequency communications. Summary of the invention

[0004] The invention provides a homogeneous inhomogeneous polyimide film material with the characteristics of low dielectric constant, low dielectric loss and low moisture absorption rate, which solves the problem that the current traditional polyimide material cannot be applied to 5G high-frequency communication technology due to substandard dielectric properties.

[0005] One of the purposes of the present invention is to provide a homogeneous inhomogeneous polyimide film, wherein the crystals in the polyimide film are mainly oriented along a direction parallel to the film surface, and the orientation factor is >0.4.

[0006] The film of the present invention is obtained from a partially crystallized polyimide material, and the crystal grains are highly oriented along a direction parallel to the film surface.

[0007] The moisture absorption rate of the polyimide film of the present invention is less than 0.5%.

[0008] Meanwhile, when tested under 10 GHz frequency conditions, the dielectric constant of the polyimide film is less than 3.0, and the dielectric loss is less than 0.005.

[0009] The homogeneous inhomogeneous polyimide film of the present invention has a crystal orientation effect, and the molecular chain segments in the polyimide film material are tightly stacked, and the distance between the molecular chains is reduced, which effectively limits the penetration and adsorption of water molecules and reduces the moisture absorption rate of the material. At the same time, the grain orientation increases the intermolecular interaction, so that the mobility of the molecular fragments under an external electric field is weakened, thereby reducing the dielectric constant and dielectric loss.

[0010] The polyimide film of the present invention has a structure shown in formula (I):

[0011]

[0012] Among them, Ar 1 At least one selected from the following structures,

[0013]

[0014]

[0015] R' 1 , R' 2 , R' 4 , R' 5 R' is independently hydrogen, methyl, trifluoromethyl, phenyl, 3 is an oxygen atom, a carbonyl group, a methylene group, a hexafluoroisopropyl group, or a sulfone group;

[0016] Ar 2 At least one selected from the following structures,

[0017]

[0018]

[0019] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 R is independently a hydrogen atom, a fluorine atom, a methyl group, a trifluoromethyl group, a trifluoromethoxy group, or a 1,1,2-trifluoro-2-(perfluoropropoxy)ethoxy group; 9 , R 10 At the same time, it is methyl or trifluoromethyl.

[0020] The second object of the present invention is to provide a method for preparing the polyimide film, comprising polymerizing diamine monomers and dianhydride monomers to obtain a polyamic acid solution, followed by imidization to form a polyimide film, and then performing a simultaneous biaxial stretching step and / or a heat treatment annealing step.

[0021] In the above preparation method, the diamine monomer is an aromatic diamine, preferably selected from 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diaminobiphenyl, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-bis(methyl)-4,4'-diaminobiphenyl, p-phenylenediamine, m-phenylenediamine, 2,3,5,6-tetrafluoro-1,4-phenylenediamine, 4,5-difluorobenzene-1,2-diamine, 2-fluoro-1,4-phenylenediamine, 2,2',3,3',5,5',6,6'-octafluoro-[1,1'-biphenyl]-4,4'-diamine, 4,4'-diamino-2,2'-diphenyl At least one of (trifluoromethoxy)benzidine, 2,2'-bis(1,1,2-trifluoro-2-(perfluoropropoxy)ethoxy)-[1,1'-biphenyl]-4,4'-diamine, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 1,3-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 1,3-bis(3-trifluoromethyl-4-aminophenoxy)benzene, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,3-bis(3'-aminophenoxy)benzene, 1,3-bis(4'-aminophenoxy)benzene, and 1,4-bis(3'-aminophenoxy)benzene.

[0022] The dianhydride monomer is an aromatic tetracarboxylic dianhydride, preferably selected from pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2'-dimethyl-3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2'-bis(trifluoromethyl)-3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2'-diphenyl-3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride , 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 5,5'-methylenebis(isobenzofuran-1,3-dione), 1,3-dioxy-1,3-bisisobenzofuran-5-yl 1,3-dioxy-1,3-bisisobenzofuran-5-carboxylate, 4,4'-(4,4'-isopropyldiphenoxy)diphthalic anhydride, and at least one of 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride).

[0023] The specific structures of some diamine monomers and dianhydride monomers that can be used in the present invention are as follows:

[0024] TFDB: 2,2'-bis(trifluoromethyl)benzidine), CAS: 341-58-2.

[0025]

[0026] DMDB: 4,4'-Diamino-2,2'-dimethylbiphenyl / 2,2'-Dimethylbenzidine 4,4'-Diamino-2,2'-dimethylbiphenyl, CAS: 84-67-3.

[0027]

[0028] BPA: 4,4'-diaminobiphenyl, CAS: 92-87-5.

[0029]

[0030] PDA: p-Phenylenediamine, CAS: 106-50-3.

[0031]

[0032] mPDA: m-Phenylenediamine, CAS: 108-45-2.

[0033]

[0034] 6FPDA: 2,3,5,6-Tetrafluoro-1,4-phenylenediamine / 2,3,5,6-Tetrafluoro-1,4-phenylenediamine, CAS: 1198-64-7.

[0035]

[0036] 2FPDA: 4,5-difluorobenzene-1,2-diamine / 2,5-difluorobenzene-1,4-diamine, CAS: 698-52-2.

[0037]

[0038] FPDA: 2-fluoro-1,4-phenylenediamine / 2-fluorobenzene-1,4-diamine, CAS: 14791-78-7.

[0039]

[0040] 3TFDB: 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl / 3,3'-bis(trifluoromethyl)benzidine).

[0041]

[0042] 3DMDB: 3,3'-bis(methyl)-4,4'-diaminobiphenyl / 3,3'-bis(methyl)benzidine).

[0043]

[0044] 8FBPA: 2,2',3,3',5,5',6,6'-octafluoro-[1,1'-biphenyl]-4,4'-diamine.

[0045]

[0046] TFMOB: 4,4'-diamino-2,2'-bis(trifluoromethoxy)-p-diaminobenzidine / 2,2'-bis-trifluoromethoxy-biphenyl-4,4'-diamine, CAS: 147835-68-5.

[0047]

[0048] TFPOB: 2,2'-bis(1,1,2-trifluoro-2-(perfluoropropoxy)ethoxy)-[1,1'-biphenyl]-4,4'-diamine.

[0049]

[0050] PMDA: Pyromellitic dianhydride, CAS: 89-32-7.

[0051]

[0052] BPDA: 3,3',4,4'-Biphenyl tetracarboxylicdiandhydride, CAS: 2420-87-3.

[0053]

[0054] DMBPDA: 2,2'-dimethyl-3,3',4,4'-biphenyltetracarboxylic dianhydride / 6,6'-dimethyl-[5,5'-biisobenzofuran]-1,1',3,3'-tetraone.

[0055]

[0056] DFBPDA: 2,2'-bis(trifluoromethyl)-3,3',4,4'-biphenyltetracarboxylic dianhydride / 6,6'-bis(trifluoromethyl)-[5,5'-biisobenzofuran]-1,1',3,3'-tetraone.

[0057]

[0058] ODPA: 3,3',4,4'-diphenyl ether tetracarboxylic anhydride / 4,4'-Oxydiphthalic anhydride, CAS: 1823-59-2.

[0059]

[0060] BTDA: 3,3',4,4'-Benzophenonetetracarboxylicdianhydride, CAS: 2421-28-5.

[0061]

[0062] BDDA: 5,5'-methylenebis(isobenzofuran-1,3-dione).

[0063]

[0064] BEDA: 1,3-dioxo-1,3-dihydroisobenzofuran-5-yl 1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylate.

[0065]

[0066] In the above preparation method, the diamine monomer and the dianhydride monomer are polymerized in a polar aprotic solvent, and the total amount of the diamine monomer and the dianhydride monomer accounts for 5-20wt% of the reaction system, preferably 7-17wt%.

[0067] In the above preparation method, the molar ratio of the dianhydride monomer to the diamine monomer is (0.970-0.997):1, preferably (0.985-0.995):1.

[0068] In the above preparation method, the polar aprotic solvent is preferably at least one selected from N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, acetonitrile, hexamethylphosphoramide, γ-butyrolactone, tetramethyl sulfone, N,N-dimethylacrylureaacetone, 1,3-dimethyl-2-imidazolidinone, pyridine, tetrahydrofuran, cyclopentane, m-cresol, and diethylene glycol dimethyl ether.

[0069] In the above preparation method, the polymerization reaction temperature is 0 to 70°C, preferably 20 to 60°C.

[0070] In the above preparation method, the imidization of the polyamic acid can be carried out by high-temperature thermal imidization or chemical imidization.

[0071] In the high-temperature thermal imidization, the imidization temperature is preferably 300 to 450°C, more preferably 320 to 430°C.

[0072] In the above preparation method, the stretching ratios in the MD and TD directions in the synchronous biaxial stretching step are both 1.05 to 1.35, preferably 1.10 to 1.30;

[0073] The stretching temperature is 15° C. below and 50° C. above the glass transition temperature of the prepared polyimide film material, preferably 10° C. below and 35° C. above the glass transition temperature of the prepared polyimide film material.

[0074] In the above preparation method, the temperature of the heat treatment annealing step is from the glass transition temperature of the prepared polyimide film material to 75° C., preferably 10° C. to 50° C. above the glass transition temperature.

[0075] The heat treatment annealing time is 50 to 350 seconds, preferably 100 to 300 seconds.

[0076] During the heat treatment annealing, the polyimide film may be fixed under bidirectional constant stress, and the bidirectional constant stress mainly plays a fixing role and is not particularly limited.

[0077] The third object of the present invention is to provide application of the polyimide film or the polyimide film material obtained by the preparation method in the field of high-frequency communication.

[0078] When applied, the frequency of electromagnetic waves used for communication is >0.45GHz.

[0079] The crystals in the homogeneous inhomogeneous polyimide film obtained in the present application are mainly oriented along the direction parallel to the film surface, with an orientation factor > 0.4. When tested under 10 GHz frequency conditions, the dielectric constant is < 3.0, the dielectric loss is < 0.005, and the moisture absorption rate is < 0.5%. It can be used for the industrial production of homogeneous inhomogeneous polyimide film materials suitable for high-frequency communication technology and downstream product applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 This is the XRD test result of the polyimide film material in Example 1.

[0081] Figure 2 This is the XRD test result of the polyimide film material in Comparative Example 1.

[0082] Figure 3 This is the XRD integration result along the orientation angle of the polyimide film material in Example 1.

[0083] Figure 4 This is the XRD integration result along the orientation angle of the polyimide film material in Comparative Example 1. DETAILED DESCRIPTION

[0084] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0085] The raw materials used in the specific implementation manner of the present invention are commercially available.

[0086] Preparation of polyimide film:

[0087] First, a non-protonic solvent such as N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide and N-methyl-2-pyrrolidone is used as a reaction medium, and a diamine monomer and a dianhydride monomer are used as reactants to form a polyamic acid solution, and the reaction temperature is 0-70°C, wherein the weight of the diamine and the dianhydride accounts for 5% to 20% of the total weight including the reaction medium and the reactants. The imidization of the polyamic acid can be implemented by high-temperature thermal imidization or chemical imidization.

[0088] [Example 1]

[0089] 26.66 g (0.083 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFDB) and 284 g of N-methyl-2-pyrrolidone (NMP) were added to a three-necked flask, and after stirring to dissolve, 21.82 g (0.074 mol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 1.79 g (0.0082 mol) of pyromellitic dianhydride (PMDA) were added, and the mixture was stirred and reacted at 60°C under nitrogen protection for 48 hours to obtain a polyamic acid solution.

[0090] After the polyamic acid solution was coated, most of the solvent was first removed at 100° C. under nitrogen protection, and then the temperature was gradually raised to 450° C. under nitrogen protection to complete imidization. The glass transition temperature of the obtained polyimide film was 363° C. The obtained film was subjected to synchronous biaxial stretching (MD stretching ratio 1.30, TD stretching ratio 1.30) at 350° C. under nitrogen protection to obtain the polyimide film of [Example 1]

[0091] [Comparative Example 1]

[0092] The polyamic acid solution preparation process and the imidization process are exactly the same as those in [Example 1], but there is no simultaneous biaxial stretching step, and the polyimide film of [Comparative Example 1] is obtained.

[0093] [Example 2]

[0094] In a three-necked flask, 12.74 g (0.060 mol) of 4,4'-diamino-2,2'-dimethylbiphenyl (DMDB), 5.06 g (0.028 mol) of 2,3,5,6-tetrafluoro-1,4-phenylenediamine (6FPDA) and 340 g of N,N-dimethylacetamide (DMAc) were added, and after stirring to dissolve, 28.21 g (0.08756 mol) of 3,3',4,4'-benzophenone tetraacid dianhydride (BTDA) was added, and the reaction was stirred at 45°C under nitrogen protection for 24 hours to obtain a polyamic acid solution.

[0095] After the polyamic acid solution was coated, most of the solvent was first removed at 100° C. under nitrogen protection, and then the temperature was gradually raised to 320° C. under nitrogen protection to complete imidization. The glass transition temperature of the obtained polyimide film was 351° C. The obtained film was annealed at 360° C. under nitrogen protection for 300 s (MD constant stress 1.0 MPa, TD constant stress 1.0 MPa) to obtain the polyimide film of [Example 2]

[0096] [Comparative Example 2-1]

[0097] The preparation process of the polyamic acid solution is exactly the same as that of [Example 2], but without the annealing step. After coating and imidization, the polyimide film [Comparative Example 2-1] is obtained.

[0098] [Comparative Example 2-2]

[0099] The preparation process of the polyamic acid solution and the imidization conditions are exactly the same as those in Example 2. The obtained film is annealed at 340°C under nitrogen protection for 300s (MD constant stress 1.0MPa, TD constant stress 1.0MPa) to obtain the polyimide film of Comparative Example 2-2.

[0100] [Comparative Example 2-3]

[0101] The preparation process of the polyamic acid solution and the imidization conditions are exactly the same as those in Example 2. The obtained film is annealed at 430°C under nitrogen protection for 300s (MD constant stress 1.0MPa, TD constant stress 1.0MPa) to obtain the polyimide film of Comparative Example 2-3.

[0102] [Example 3]

[0103] In a three-necked flask, 16.01 g (0.050 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFDB) and 286 g of N,N-dimethylacetamide (DMAc) were added, and after stirring to dissolve, 9.60 g (0.044 mol) of pyromellitic dianhydride (PMDA) and 2.71 g (0.0052 mol) of 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride) (BPADA) were added, and the mixture was stirred and reacted at 20°C under nitrogen protection for 48 hours to obtain a polyamic acid solution.

[0104] After the polyamic acid solution was coated, most of the solvent was first removed at 100° C. under nitrogen protection, and then the temperature was gradually raised to 400° C. under nitrogen protection to complete imidization. The glass transition temperature of the obtained polyimide film was 360° C. The obtained film was synchronously biaxially stretched at 390° C. under nitrogen protection (MD stretching ratio 1.10, TD stretching ratio 1.10), and then the polyimide film of [Example 3] was obtained.

[0105] [Comparative Example 3-1]

[0106] The preparation process of the polyamic acid solution is exactly the same as that of [Example 3], but without the synchronous biaxial stretching step. After coating and imidization, the polyimide film [Comparative Example 3-1] is obtained.

[0107] [Comparative Example 3-2]

[0108] The preparation process of the polyamic acid solution is exactly the same as that of [Example 3]. After coating and imidization, the obtained film is subjected to synchronous biaxial stretching (MD stretching ratio 1.10, TD stretching ratio 1.10) at 335°C under nitrogen protection to obtain [Comparative Example 3-2] polyimide film.

[0109] [Comparative Example 3-3]

[0110] The preparation process of the polyamic acid solution is exactly the same as that of [Example 3]. After coating and imidization, the obtained film is subjected to synchronous biaxial stretching (MD stretching ratio 1.10, TD stretching ratio 1.10) at 420°C under nitrogen protection to obtain [Comparative Example 3-3] polyimide film.

[0111] [Example 4]

[0112] In a three-necked flask, 8.01 g (0.025 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (TFDB), 7.43 g (0.035 mol) of 4,4'-diamino-2,2'-dimethylbiphenyl (DMDB) and 241 g of N,N-dimethylacetamide (DMAc) were added, and after stirring and dissolving, 17.48 g (0.0594 mol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added, and the reaction was stirred at 35° C. under nitrogen protection for 48 hours to obtain a polyamic acid solution.

[0113] After the polyamic acid solution is coated, most of the solvent is first removed at 100° C. under nitrogen protection, and then the temperature is gradually raised to 350° C. under nitrogen protection to complete imidization, and the glass transition temperature of the obtained polyimide film is 375° C. The obtained film is first subjected to synchronous biaxial stretching at 370° C. under nitrogen protection (MD stretching ratio 1.30, TD stretching ratio 1.30), and then annealed at 390° C. under nitrogen protection for 100s (MD constant stress 1.0 MPa, TD constant stress 1.0 MPa) to obtain the polyimide film of [Example 4]

[0114] [Example 5]

[0115] The preparation process of the polyamic acid solution and the imidization process are exactly the same as those in [Example 4]. After coating and imidization, the obtained film is first annealed at 390°C under nitrogen protection for 100s (MD constant stress 1.0MPa, TD constant stress 1.0MPa), and then subjected to synchronous biaxial stretching at 370°C under nitrogen protection (MD stretching ratio 1.30, TD stretching ratio 1.30) to obtain the polyimide film of [Example 5].

[0116] The coefficient of thermal expansion (CTE), glass transition temperature, crystallinity, grain orientation, dielectric constant, dielectric loss and moisture absorption of the polyimide film obtained above were measured by the following method:

[0117] CTE: The samples were tested using a thermomechanical analyzer at a load of 0.05N and a heating rate of 10°C / min. The CTE was obtained by calculating the average value of the dimensional change of the samples in the range of 50°C to 200°C.

[0118] X-ray diffraction test: The prepared polyimide film was tested by grazing incidence X-ray diffraction (reflection mode) and transmission X-ray diffraction (projection mode), respectively.

[0119] Crystallinity: calculated by the following equation,

[0120] Cr(%)=S c / (S c +S a )

[0121] Where Cr is the percentage crystallinity; S c is the integrated area of ​​the crystallization peak; S a is the integrated area of ​​the amorphous peak. c With S a ) was obtained by fitting the X-ray diffraction data using Origin software.

[0122] Grain orientation: By analyzing the X-ray diffraction data obtained in the reflection mode and the transmission mode, the distribution of different crystal planes in the film plane and in the direction perpendicular to the film plane is judged to obtain the grain orientation.

[0123] Orientation factor: In order to further quantitatively characterize the degree of grain orientation, the sample orientation factor is calculated by the following formula:

[0124]

[0125] Where f is the orientation factor, is the orientation parameter,

[0126]

[0127] in is the azimuth, is the XRD diffraction intensity at a specific azimuth angle.

[0128] Dielectric constant and dielectric loss: According to IPC-TM-650-2.5.5.9 standard, the prepared polyimide film material was tested at 10 GHz using the resonant cavity method.

[0129] Moisture absorption rate: The moisture absorption rate of the prepared polyimide film was tested according to the IPC-TM-650-2.6.2 standard.

[0130] Determination of glass transition temperature of polyimide film: The sample was tested using a thermomechanical analyzer under the conditions of a load of 0.05 N and a heating rate of 10° C. / min.

[0131] The results of testing the embodiments and comparative examples by the above method are summarized in Table 1.

[0132] Table 1 Test results of various embodiments and comparative examples

[0133]

[0134] It can be seen from the data in Table 1 that grain orientation has a huge effect on reducing the dielectric constant, dielectric loss and moisture absorption rate of the material. Compared with the comparative example in which the grains are not oriented, the embodiments with grain orientation characteristics all have a dielectric constant of <3.0, a dielectric loss of <0.005 and a moisture absorption rate of <0.5%. This is mainly because after the grain orientation, the molecular chains become tightly stacked and the distance between the molecular chains decreases, making it difficult for water molecules to penetrate. At the same time, because the grain orientation increases the intermolecular interaction, the mobility of the molecular fragments under the external electric field is weakened, so the dielectric constant and dielectric loss decrease.

[0135] At the same time, by comparing the test results of Examples 1, 2, 3 with Comparative Examples 1, 2-1, and 3-1 in Table 1, it can be seen that the crystallinity and grain orientation of the polyimide film can be improved by post-processing methods such as synchronous biaxial stretching and high-temperature annealing, thereby greatly improving the dielectric properties and moisture absorption rate of the material. This may be due to the enhanced activity of the molecular chain segments under high temperature conditions, the crystallization trend becomes larger, and at the same time, under the action of external force, the grains selectively orient along the direction of the external force. By comparing the test results of Example 2 with Comparative Examples 2-2 and 2-3 in Table 1 and Example 3 with Comparative Examples 3-2 and 3-3, it can be seen that the choice of post-processing temperature plays a key role in improving the final material performance. Whether the annealing or stretching temperature is too high or too low, the purpose of effectively improving the material performance cannot be achieved.

[0136] In addition, by Figure 1 and Figure 2 It can be seen that without post-treatment such as synchronous biaxial stretching or high temperature annealing, the crystallization of the polyimide film of Comparative Example 1 is very weak, and there is no observable grain orientation. After biaxial stretching, the crystallinity of Example 1 is greatly improved, and it can be observed that the diffraction patterns of different positions and intensities appear in the reflection mode and the transmission mode in the XRD test. This is because the XRD reflection mode mainly observes the crystallization and molecular arrangement in the direction perpendicular to the film surface, while the transmission mode mainly observes the crystallization and arrangement in the direction parallel to the film surface. After analysis, it is known that the diffraction peak detected in the embodiment polyimide film material in the reflection mode is mainly contributed by the (hk0) crystal plane, and the diffraction peak detected in the transmission mode is mainly contributed by the (00l) crystal plane, thus proving that the crystallization of the embodiment polyimide film material is mainly oriented inward along the direction parallel to the film surface.

[0137] At the same time, the XRD data of the embodiment and the comparative example in the reflection mode were integrated along the azimuth angle, and the results were as follows: Figure 3 and Figure 4 Compared with the comparative example, the diffraction intensity of Example 1 at the azimuth angle of about 0 degrees is significantly higher than that at other azimuth angles, which proves that most of the crystals in the polyimide film material of Example 1 are parallel to the film plane and have obvious crystal orientation.

Claims

1. A homogeneous inhomogeneous polyimide film, wherein the crystals in the polyimide film are mainly oriented in a direction parallel to the film surface, and the orientation factor is >0.4; the preparation method of the polyimide film comprises polymerizing a diamine monomer and a dianhydride monomer to obtain a polyamic acid solution, followed by imidization to form a polyimide film, and then performing a synchronous biaxial stretching step and / or a heat treatment annealing step, wherein the stretching temperature is 15°C below and 50°C above the glass transition temperature of the polyimide film material; the temperature of the heat treatment annealing step is 75°C above the glass transition temperature of the polyimide film material; the polyimide has a structure shown in formula (I): in, Ar1 is selected from at least one of the following structures, R ’ 1. R ’ 2. R ’ 4. R ’ 5 is independently hydrogen, methyl, trifluoromethyl, or phenyl, R ’ 3 is an oxygen atom, a carbonyl group, a methylene group, a hexafluoroisopropyl group, or a sulfone group; Ar2 is selected from at least one of the following structures, R1, R2, R3, R4, R5, R6, R7, and R8 are independently hydrogen atoms, fluorine atoms, methyl groups, trifluoromethyl groups, trifluoromethoxy groups, or 1,1,2-trifluoro-2-(perfluoropropoxy)ethoxy groups; R9, R 10 At the same time it is methyl or trifluoromethyl.

2. The polyimide film according to claim 1, characterized in that: The moisture absorption rate of the polyimide film is less than 0.5%; and / or, Under the condition of 10 GHz frequency, the dielectric constant of the polyimide film is less than 3.0, and the dielectric loss is less than 0.

005.

3. A method for preparing a polyimide film according to any one of claims 1 to 2, comprising polymerizing a diamine monomer and a dianhydride monomer to obtain a polyamic acid solution, followed by imidization to form a polyimide film, and then performing a simultaneous biaxial stretching step and / or a heat treatment annealing step.

4. The method for preparing a polyimide film according to claim 3, wherein: The diamine monomer is an aromatic diamine; and / or, The dianhydride monomer is an aromatic tetraacid dianhydride.

5. The method for preparing a polyimide film according to claim 4, characterized in that: The diamine monomer is selected from 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diaminobiphenyl, 3,3'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-bis(methyl)-4,4'-diaminobiphenyl, p-phenylenediamine, m-phenylenediamine, 2,3,5,6-tetrafluoro-1,4-phenylenediamine, 4,5-difluorobenzene-1,2-diamine, 2-fluoro-1,4-phenylenediamine, 2,2',3,3',5,5',6,6'-octafluoro-[1,1'-biphenyl]-4,4'-diamine, 4,4'-diamino-2,2'-bis(trifluoromethoxy)-p-phenylenediamine at least one of biphenyl, 2,2'-bis(1,1,2-trifluoro-2-(perfluoropropoxy)ethoxy)-[1,1'-biphenyl]-4,4'-diamine, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 1,3-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 1,3-bis(3-trifluoromethyl-4-aminophenoxy)benzene, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,3-bis(3'-aminophenoxy)benzene, 1,3-bis(4'-aminophenoxy)benzene, and 1,4-bis(3'-aminophenoxy)benzene; and / or The dianhydride monomer is selected from pyromellitic acid dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 2,2'-dimethyl-3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 2,2'-bis(trifluoromethyl)-3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 2,2'-diphenyl-3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydride, 3,3' , at least one of 4,4'-dibenzophenone tetracarboxylic dianhydride, 5,5'-methylenebis(isobenzofuran-1,3-dione), 1,3-dioxy-1,3-diisobenzofuran-5-yl 1,3-dioxy-1,3-diisobenzofuran-5-carboxylate, 4,4'-(4,4'-isopropyldiphenoxy)diphthalic anhydride, and 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride).

6. The method for preparing a polyimide film according to claim 3, characterized in that: The diamine monomer and the dianhydride monomer are polymerized in a polar aprotic solvent, wherein: The total amount of the diamine monomer and the dianhydride monomer accounts for 5 to 20 wt % of the reaction system; and / or, The molar ratio of the dianhydride monomer to the diamine monomer is (0.970-0.997):1; and / or, The polymerization reaction temperature is 0-70°C.

7. The method for preparing a polyimide film according to claim 6, wherein: The total amount of the diamine monomer and the dianhydride monomer accounts for 7 to 17 wt % of the reaction system; and / or, The molar ratio of the dianhydride monomer to the diamine monomer is (0.985-0.995):1; and / or, The polymerization reaction temperature is 20-60°C.

8. The method for preparing a polyimide film according to claim 3, characterized in that: The stretching ratios in the MD and TD directions in the synchronous biaxial stretching step are both 1.05 to 1.35; and / or, The stretching temperature is 15° C. below and 50° C. above the glass transition temperature of the polyimide film material.

9. The method for preparing a polyimide film according to claim 8, characterized in that: The stretching ratios in the MD and TD directions in the synchronous biaxial stretching step are both 1.10 to 1.30; and / or, The stretching temperature is 10° C. below and 35° C. above the glass transition temperature of the polyimide film material.

10. The method for preparing a polyimide film according to claim 3, characterized in that: The temperature of the heat treatment annealing step is 75° C. or higher than the glass transition temperature of the polyimide film material; and / or, The heat treatment time is 50 to 350 seconds.

11. The method for preparing a polyimide film according to claim 10, characterized in that: The temperature of the heat treatment annealing step is 10°C to 50°C above the glass transition temperature of the polyimide film material; and / or, The heat treatment time is 100s to 300s.

12. Use of the polyimide film according to any one of claims 1 to 2 or the polyimide film obtained by the preparation method according to any one of claims 3 to 11 in the field of high-frequency communication.

13. The use of the polyimide film according to claim 12 in the field of high frequency communication, characterized in that: The frequency of electromagnetic waves used for communication is >0.45GHz.

Citation Information

Patent Citations

  • Polyimide film, and preparation method and use thereof

    CN110092908A